2019
DOI: 10.31729/jnma.4642
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Working Memory Impairment in Drug Naive Schizophrenic Patients in a Tertiary Care Hospital

Abstract: Introduction: Schizophrenia is a mental disorder in which clear consciousness and the intellectual capacity are usually maintained, although certain cognitive deficits may evolve in the course of illness. Working memory impairment in schizophrenia affects the course, outcome, and quality of life of the patient significantly. The aim of the study was to find out the prevalence of working memory impairment in drug naive schizophrenic patients. Methods: This descriptive cross-sectional study was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…This study showed the prevalence of cognitive impairment among patients with schizophrenia was 89.3% which was comparable to the estimates of most other studies [19] [17]. While the prevalence rates of many studies ranged between 80-90% [19], a study from the USA reported the prevalence as 98% [20]. Published data regarding this topic in Asian countries is scarce, a study from Nepal found the prevalence of working memory impairment in a sample of Nepalese antipsychotic-naive patients with schizophrenia to be 86.7% [19].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study showed the prevalence of cognitive impairment among patients with schizophrenia was 89.3% which was comparable to the estimates of most other studies [19] [17]. While the prevalence rates of many studies ranged between 80-90% [19], a study from the USA reported the prevalence as 98% [20]. Published data regarding this topic in Asian countries is scarce, a study from Nepal found the prevalence of working memory impairment in a sample of Nepalese antipsychotic-naive patients with schizophrenia to be 86.7% [19].…”
Section: Discussionsupporting
confidence: 89%
“…This study showed the prevalence of cognitive impairment among patients with schizophrenia was 89.3% which was comparable to the estimates of most other studies [19] [17]. While the prevalence rates of many studies ranged between 80-90% [19], a study from the USA reported the prevalence as 98% [20].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study showed the prevalence of cognitive impairment among patients with schizophrenia was 89.3% which was comparable to the estimates of most other studies [ 20 , 22 ]. While the prevalence rates of many studies ranged between 80 and 90% [ 22 ], a study from the USA reported the prevalence as 98% [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…This study showed the prevalence of cognitive impairment among patients with schizophrenia was 89.3% which was comparable to the estimates of most other studies [ 20 , 22 ]. While the prevalence rates of many studies ranged between 80 and 90% [ 22 ], a study from the USA reported the prevalence as 98% [ 23 ]. Published data regarding this topic in Asian countries is limited, a study from Nepal found the prevalence of working memory impairment in a sample of Nepalese antipsychotic-naive patients with schizophrenia to be 86.7% [ 22 ].…”
Section: Discussionsupporting
confidence: 89%